Growth of Red Chili in Early Generative Stage to Application of Ameliorants and Mycorrhizal Biofertilizer During Shallow Water Table (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
Indonesia has a lot of swamp land that is still classified as marginal and has not been optimally utilized for its development. One of the efforts that can be made to increase the productivity of Lebak swamp land is by providing amelioran and mikorza biofertilizer. Red chili is a plant that can be cultivated in swampland. The purpose of the study was to determine the growth response and high level of resilience of red chili plants (Capsicum annuum L.) by applying a combination of mycorrhizal and amelioran biofertilizers in shallow groundwater table conditions in the early generative phase. This research was carried out in the Laboratory and Experimental Garden of the Agrotechnology Study Program, Faculty of Plant and Animal Sciences, Bina Insan University, from July to November 2024. The research design applied was a two-factor complete randomized design with the treatment of the first factor of shallow groundwater level condition (S), the second factor of a combination of ameliorant and mycorrhizal biofertilizer (M). The results showed that the treatment of shallow groundwater surface conditions had a significant effect on plant height, stem diameter, number of leaves, root length, and dry weight of chili plants, while the treatment of amelioran and mycorrhizal biofertilizer showed no significant effect on all observation variables. Shallow groundwater table conditions and the combination of ameliorant + mycorrhizal biofertilizer showed that the results of different interactions were very real only at plant height.